Foreign experience in the system of personnel management in the state civil service and its adaptation in Russian practice - I. A. Dimaeva; D. Yu. Znamenskiy (Вестник университета)
An analysis of the foreign experience ofpublic service and the possibility of its use in Russia has been performed. The research is aimed at studying foreign experience of working with public administration personnel in order to make recommendations for improving the Russian personnel policy in the public service. The object of the study is public service in the world practice. The subject of the research is personnel policy in the public service offoreign countries. The positions of Russian and foreign scientists in this field of research have been summarized. The main trends of personnel policy in the public service in foreign countries have been highlighted. Public service in countries such as England, Germany, the USA, France and Japan have been analysed.